Studying the Effect of Non-Linear Loads Harmonics on Electric Generator Power Rating Selection - EL Sebaay, Ahmed; Ramadan, Mahmoud; Adma, Maged A. Abu (European Scientific Journal, ESJ, 2017)
Non-linear loads connected to an electric power system produce Harmonic currents, harmonics are introduced into the system in the form of currents whose frequencies are the integral multiples of the fundamental power system frequency (50/60 Hz). The harmonic currents interact with the supply system impedance causing distortions in supply output voltage and current, which has a very bad effect on all other loads connected to the system and the power supply itself, such as overheating, increasing powers losses in the system, and malfunction of protection and control devices connected to the system. This paper presents a study to analyze the effect of voltage and current harmonics resulting from non-linear loads such as variable frequency drive, uninterruptable power supply, and battery chargers on operation and power rating of synchronous generator. The study introduces an optimized method for selecting the suitable generator power rating to withstand harmful harmonics effects for a safe operation of the generator, saving its lifetime, and to improve the power quality of the power system. The method depends on analyzing the effect of increasing the supply generator power rating on the THVD produced from non-linear loads harmonics connected to the system. By calculating the THVD for each case of a generator power rating, a mathematical relationship between generator power rating and TVHD can be found. So, the relationship between generator power rating and total harmonic distortion in the power system will be discussed clearly.